2003
DOI: 10.1556/smus.44.2003.3-4.5
|View full text |Cite
|
Sign up to set email alerts
|

Movement Cognition and Dance Notation

Abstract: It can be stated that dance notation was proved to be an established tool for dance research and dance education in understanding and analyzing movement. This theorem is especially valid in cases where, the structure of dance is amorphous, the units of movement sequences differ from that of the accompanying music, the tempo of the dance is high. Dance notation is used rather isolated in the field of traditional dance in Hungary, mainly in dance research. In the light of the research introduced above it is high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…However, what becomes clear is that, if the student participates and does not passively receive information/knowledge, then the possibility of better and more effective learning is much greater (Kassing & Jay, 2003) since the act of moving with the senses requires an advanced range of intellectual processes (Smith-Autard, 2002;Warburton, 2000). This view is reinforced by research which has shown that the holistic involvement of the body in a mutual process of knowledge transfer can lead to better and more substantial learning of the technique itself (Dils, 2007a;Green, 2007), by transferring the weight of the teaching process from a sterile mimetic learning of a technique to a substantial and in-depth knowledge and understanding of movement (Fügedi, 2003). Moreover, students' involvement in dance literacy practices, through the triptych of "participate", "create" and "observe" can improve the technique in a specific dance genre (Jusslin, 2019).…”
Section: B Research Findings Of the Second Action Research Cyclementioning
confidence: 99%
“…However, what becomes clear is that, if the student participates and does not passively receive information/knowledge, then the possibility of better and more effective learning is much greater (Kassing & Jay, 2003) since the act of moving with the senses requires an advanced range of intellectual processes (Smith-Autard, 2002;Warburton, 2000). This view is reinforced by research which has shown that the holistic involvement of the body in a mutual process of knowledge transfer can lead to better and more substantial learning of the technique itself (Dils, 2007a;Green, 2007), by transferring the weight of the teaching process from a sterile mimetic learning of a technique to a substantial and in-depth knowledge and understanding of movement (Fügedi, 2003). Moreover, students' involvement in dance literacy practices, through the triptych of "participate", "create" and "observe" can improve the technique in a specific dance genre (Jusslin, 2019).…”
Section: B Research Findings Of the Second Action Research Cyclementioning
confidence: 99%